Cosmological Evolution of a Dark Energy Model with Non-Linear Interaction. (2016)
In this paper it is considered a holographic dark energy model with a non-linear interaction between the component of dark energy and dark matter in a FRW type flat universe. In this context, the cosmological evolution of the universe is analyzed taking into account the behavior of the deceleration parameters q and the equation of state wL. From this analysis it follows that the universe has a phase of accelerated expansion in late times. It also notes that in this scenario the dark energy density will have a Big Rip type singularity in the future. Finally, it is compared the model with currently available data for H(z).